2020
DOI: 10.20944/preprints202011.0225.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Coulomb Symmetry and a Universal Representation of Rydberg Spectral Line Shapes in magnetized Plasmas

Abstract: A new method of line shape calculations of hydrogen-like atoms in magnetized plasmas is presented. This algorithm makes it possible to solve two fundamental problems in the broadening theory: the analytical description of the radiation transition array between excited atomic states and account of a thermal ion motion effect on the line shapes formation. The solution to the first problem is based on the semiclassical approach to dipole matrix elements calculations and the us… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This model is widely used 15 for spectral line shape calculations in plasmas (see e.g. [4][5][6][7][8][9]). It was shown that the 16 FFM is equivalent to the method of the quantum kinetic equation [10].…”
Section: Introduction 10mentioning
confidence: 99%
See 1 more Smart Citation
“…This model is widely used 15 for spectral line shape calculations in plasmas (see e.g. [4][5][6][7][8][9]). It was shown that the 16 FFM is equivalent to the method of the quantum kinetic equation [10].…”
Section: Introduction 10mentioning
confidence: 99%
“…The examination of the FFM consists in the comparsion of the CT formula ( 12) with the expression (9). In the integrand of ( 10) we will substitute the static profile (14).…”
mentioning
confidence: 99%